Holmium Laser Lithotripsy in the New Stone Age: Dust or Bust? - Aldoukhi, Ali H.; Roberts, William W.; Hall, Timothy L.; Ghani, Khurshid R. (Frontiers in Surgery, 2017)
Modern day holmium laser systems for ureteroscopy provide users with a range of settings, namely pulse energy (PE), pulse frequency (Fr), and pulse width (PW). These variables allow the surgeon to choose different combinations that have specific effects on stone fragmentation during URS lithotripsy. Contact laser lithotripsy can be performed using fragmentation or dusting settings. Fragmentation employs settings of Low Fr and high PE (LoFr-HiPE) to break stones which are then extracted with retrieval devices. Dusting is the utilization of high Fr and low PE (HiFr-LoPE) settings to break stones into sub-millimeter fragments for spontaneous passage without the need for basket retrieval. Use of the long PW mode during lithotripsy can reduce stone retropulsion and is increasingly available in new generation lasers. During non-contact laser lithotripsy, stone fragments are rapidly pulverized in a calyx in laser bursts that result in stones breaking into fine fragments. In this review, we discuss the effect of different holmium laser settings on stone fragmentation, and the clinical implications in a very much evolving field.